Mechanisms of cadmium-stress avoidance by selenium in tomato plants - Alves, Leticia Rodrigues [UNESP]; Prado, Emilaine Rocha [UNESP]; de Oliveira, Reginaldo [UNESP]; Santos, Elcio Ferreira; Lemos de Souza, Ivana [UNESP]; dos Reis, André Rodrigues [UNESP]; Azevedo, Ricardo Antunes; Gratão, Priscila Lupino [UNESP] (Springer Nature, 2020)
Cadmium (Cd) is probably the most damaging metal to plant species; with a long biological half-life, it can be taken up by plants, disrupting the cell homeostasis and triggering several metabolic pathways. Selenium (Se) improves plant defence systems against stressful conditions, but the biochemical antioxidant responses to Cd stress in tomato plants is poorly understood. To further address the relationship of Cd-stress responses with Se mineral uptake, Cd and Se concentration, proline content, MDA and H2O2 production, and the activity of SOD, APX, CAT and GR enzymes were analyzed in Micro-Tom (MT) plants submitted to 0.5 mM Cd. The results revealed different responses according to Se combination and Cd application. For instance, roots and leaves of MT plants treated with Se exhibited an increase in dry mass and nutritional status, exhibited lower proline content and higher APX and GR activities when compared with plants with no Se application. Plants submitted to 0.5 mM Cd, irrespective of Se exposure, exhibited lower proline, MDA and H2O2 content and higher SOD, CAT and GR activities. Selenium may improve tolerance against Cd, which allowed MT plants exhibited less oxidative damage to the cell, even under elevated Cd accumulation in their tissues. The results suggest that Se application is an efficient management technique to alleviate the deleterious effects of Cd-stress, enhancing the nutritional value and activity of ROS-scavenging enzymes in tomato plants.
Keywords: Abiotic stress; Antioxidant metabolism; Selenium; Solanum lycopersicum